Design of 24VDC to 240VAC inverter for running stand fan - Siti Mariam Ghazali (School of Electrical System Engineering, University Malaysia Perlis, 2011)
Power inverters, regardless of size, are typically constructed of a DC - AC converter. A square wave output will be obtained through the use of a controller and high frequency switching. The controller will be used to digitally drive the transistors on the inverter side of the circuit. This will result in pulses at precise time intervals. The slope and magnitude of the output signal will be exact, as opposed to the unstable signal generated by other power inverters that use analog technology. This power inverter will operate using high frequency switching technology. The harmonics that are produced using high frequency switching will include those near the range of the switching frequency, and those that are of a relatively higher order than the 50 Hz frequency. This translates into a much cleaner output signal. Also, the use of high frequency switching will minimize the size of parts used for the construction of the inverter. Future work could be done to further improve efficiency, total harmonic distortion, and size of the power inverter. With these additional improvements, the standard could be raised for future DC/AC power supplies.